RELATIONSHIP BETWEEN PARENTAL OCCUPATION, HOME ENVIRONMENT AND ACADEMIC PERFORMANCE OF PUBLIC SENIOR SECONDARY SCHOOL STUDENTS IN SOKOTO STATE, NIGERIA - Umar, Maimuna Rabo (Sokoto Educational Review, 2017)
This paper discussed the relationship between parental background support in relation to occupation, home environment and students’ academic performance. The research design adopted for this study was correlation research design. The study was based on Conflict theory, which sees the purpose of education as a means of maintaining social inequality and preserving the power of those who dominate the society. The study was carried out using questionnaire, achievement test and focus group discussions, the questionnaire was researcher designed and it was based on closed ended questions with options of A,B,C,D,E and F, respectively all the instruments were validated by the supervisory team and the reliability was obtained by pilot testing of questionnaire and test-retest for achievement test and arrived at co-efficient alpha 0.83 and 0.81 respectively. The population was also all the public senior secondary school students in Sokoto state. A total number of twelve public senior secondary schools, with three thousand four hundred and twenty eight (3,428) as the population of SS II students, were purposively selected within the six educational zones to represent the total population. Qualitative data collected were analyzed through thematic analysis by coding and transcription, while the quantitative data were analyzed using Pearson Product Moment Correlation Co-efficient. The major findings of the study were: Parental background support in relation to occupation has relationship with student’s academic performance. Parental background support in relation to home environment has relationship with student’s academic performance. The study recommended that: parents that are found to be of lower socio-economic status who can not provide support for the academic activities of their children, should utilize those community development programmes meant for poverty eradication and skill acquisition, such as National Poverty Eradication Programme (NAPEP), family support programme, agricultural loan scheme and so on, that will provide financial support and job security. It was also recommended that parents should endeavour to provide required academic support at home such as parental commitment and material support. That is to be fully involved in their children academic activities and to provide study facilities at home, which include teaching and learning materials. This will enhance good academic performance.